'It felt like I was giving a present to myself': an exploration of service-users' experience of developing self-compassion - Lineker, Jasmine Mary (2013)
This thesis explored service-users' experience of developing self-compassion using Compassionate Mind Training (CMT). A systematic review of the existing literature on compassion and compassion-based interventions identified the primarily focused of research has been on symptom outcome measures utilizing quantitative approaches. No study that explored the experiences and processes of developing self-compassion was identified.